Analisis Parameter Spesifik dan Nonspesifik Simplisia Daun Bawang Merah (Allium cepa L.): Analysis of Specific and Nonspecific Parameters of Shallot (Allium cepa L.) Leaves Simplicia - Neneng Dwi Yana; Burhanudin Gummay; Mauritz Pandapotan Marpaung (KOVALEN: Jurnal Riset Kimia, 2022)
Shallots are natural ingredients that are used as food enhancers for food and traditional medicines. This study aimed to analyze the specific and non-specific parameters of shallot (Allium cepa L.) Simplicia. Analysis of simplicia specific parameters in the form of material identity, organoleptic, macroscopic, and microscopic examination, levels of water-soluble extracts and ethanol soluble extracts while non-specifically in the form of a percentage of drying loss, water content, total ash, acid insoluble ash, and water-insoluble ash. The results of the research on specific parameters gave a yellowish-green simplicia color, a distinctive odor, in the form of powder, macroscopic examination of leeks elongated cylindrical, small round and hollow like a pipe, blunt leaf base, pointed leaf tip, green color, microscopic examination contained cover cells, gaps and epidermal cells, the levels for water-soluble extracts were 8.81±2.12%, the levels of ethanol-soluble compounds were 5.64±2.91%. The results of the study of non-specific parameters, the percentage of drying shrinkage was 0.89±0.57%, water content was 0.89±0.34%, total ash was 12.97±0.34%, acid-insoluble ash was 6.44±2.12%, and the water-insoluble ash content was 8.03±0.84%.